Growth of three indigenous timber species for enrichment planting in Ayer Hitam Forest Reserve, Selangor, Malaysia - Ishak, Mohamad Fakhri (2013)
Forest gap opening due to natural or anthropogenic factors affects the growth of regenerated plants. It takes a long period to rehabilitate this disturbed area and it is mostly dominated by pioneer species. Therefore, a study to determine the survival rate, basal diameter and total height of three timber species based on different gap sizes and to determine the most suitable species for gap planting techniques was conducted in Ayer Hitam Forest Reserve, Selangor. This study was set up in Complete Randomized Design. Four plots were established with a 1 ha for each plot. In this study each plot represented a different planting design. Number and size of subplots for each plot varies depending on planting design. Plot 1 comprised nine subplots of 10 m x 10 m, Plot 2 has nine subplots of 20 m x 20 m, Plot 3 has five subplots of 10 m x 10 m and Plot 4 has five subplots of 20 m x 20 m. The mean percentage of canopy openness in plots 1, 2, 3 and 4 were 17.34%, 21.09%, 15.87% and 19.74%, respectively. Three species of dipterocarp namely Anisoptera marginata, Shorea assamica and Shorea platyclados were planted for this research. Data on growth for these species were measured for a period of one year. Soil in this area is in moderately acidic. Total N, available P and cation exchange capacity (CEC) are low, while exchangeable K, Ca and Mg are very low. One year after planting, A. marginata showed the best survival rate in all plots followed by S. assamica and S. platyclados. Percentage survival of species were 96%, 97%, 100% and 99%, respectively for Plot 1, 2, 3 and 4 for A. marginata; 52%, 86%, 67% and 91%, respectively for Plot 1, 2, 3 and 4 for S. assamica; and 33%, 77%, 53% and 85%, respectively for Plot 1, 2, 3 and 4 for S. platyclados. In term of basal diameter increment, no significant difference (p>0.05) was observed between species and plots. Shorea platyclados showed the best growth increment in total height compared to A. marginata and S. assamica at 36.15±2.08 cm, 23.79±1.28 cm and 13.05±0.92 cm, respectively. There was significant difference (p<0.01) between species. However, there was no significant difference (p>0.05) was observed between plots. The study also revealed that total leaf area was not significantly different (p>0.05) between species and plot. Overall, S. platyclados was found to be the best species compared to A. marginata and S. assamica in performance of growth increment. Study using various gap sizes should be conducted in the future to determine more accurately the suitable gap size for selected tree species. In addition, observation of pests and diseases should be done. Implementation of fertilizer is also required in support the growth increment of the tree. Besides that, observations on these studies should involve longer duration in order to have significant effects on all the parameters measured.